2010
DOI: 10.1007/s00580-010-1029-y
|View full text |Cite
|
Sign up to set email alerts
|

Coagulase gene polymorphism of Staphylococcus aureus isolated from clinical and sub-clinical bovine mastitis in Isfahan and Chaharmahal va Bakhtiari provinces of Iran

Abstract: Mastitis is a common disease in dairy cattle and is an inflammatory response of the breast tissue to bacterial attack to this tissue. Mastitis causes considerable loss to the dairy industry, among the several bacterial pathogens that can cause mastitis; Staphylococcus aureus is probably the most lethal agent because it causes chronic and deep infection in the mammary glands that is extremely difficult to cure. Several virulence factors including coagulase gene are produced by S. aureus and may contribute to it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
12
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 13 publications
9
12
1
3
Order By: Relevance
“…The genotype I was the predominant genotype. These findings are in accordance with a previous study by Momtaz et al in this region [19]. In another report by Saei et al [20] in Tabriz and Urmia regions of Iran, similar results have been observed.…”
Section: Discussionsupporting
confidence: 93%
“…The genotype I was the predominant genotype. These findings are in accordance with a previous study by Momtaz et al in this region [19]. In another report by Saei et al [20] in Tabriz and Urmia regions of Iran, similar results have been observed.…”
Section: Discussionsupporting
confidence: 93%
“…[ 6 ] recorded amplicon with a size of approximately 980 bp for all 34 S. aureus . Likewise, other workers [ 26 - 28 ] also found amplicons of same sizes with no polymorphism. Akineden et al .…”
Section: Discussionmentioning
confidence: 59%
“…The high prevalence in the present study may be correlated to the transmission of infection by milker's hands, contaminated equipments and bad hygienic environment in small holder cows [25]. Several virulence factors were produced by S. aureus, including Coagulase protein, which is important in the pathogenicity [26] through turn fibrinogen to fibrin, then lead to abscess formation and persistence of microorganism in host tissue [27].Coagulase protein is considered to be a virulence factor in intrammmary infection and can be used as a simple and effective method for typing of S. aureus isolates from bovine mastitis. [28].…”
Section: Discussionmentioning
confidence: 62%
“…This finding agree with [30] achieved that S. aureus isolates give 5 different PCR products of Coa gene. Furthermore, [26] stated that coagulase gene had different PCR products indicating the polymorphism of the gene. Moreover [28]showed amplification of the coa gene of S. aureus isolates from mastitic cow produces 27 different PCR-products, which ranged from 579 to 1442 bp.…”
Section: Discussionmentioning
confidence: 99%